Improve Student Engagement and Collaboration with Kahoot! - Mustangin, Muhammad (STMIK Komputama Majenang, 2019)
Technology is very popular media for learning today. For English foreign language (EFL) learners, the interesting and comprehensible media of learning is much needed. Game learning (GL) is one of integrated learning activities and will always been an integrated approach of ELT as foreign and second language for learning process. This paper is based on the research which conducted in STMIK Komputama Majenang. The researcher did the survey by giving questionnaire. The respondent is some students from Sistem Informasi and Teknik Informasi students, which is taken by Google form. Besides using the questionnaire, the researcher was also got observation from in depth interview with some EFL learners, the native lecture who teaches English, and also did literature review from some books. The result of the research then gives some evidences those EFL learners’ difficulties in engaging the English learning motivation. It can be seen from the data that all them (51.5% or 23) are agree for using this aps is helpful to encourage their vocabulary. It also mentions that 73.3% or 33 students approved to use kahoot! to enrich their vocabulary. The students also fell fun to use this media. It shows from the result that 64.4% or 29 students stated less stressful. The most interesting is that almost of the students are enjoyed to learning English by this media (53%).